ANALISIS INFEKSI MALWARE PADA PERANGKAT ANDROID DENGAN METODE HYBRID ANALYSIS - Asep Solahudin Rusdi; Nur Widiyasono; Heni Sulastri (Teknik Informatika, 2019)
Android is the most widely used operating system in the world with a percentage of 76.82% in the Android operating system market share. This fact makes the developers of malicious software (malware) make mobile phone users with the Android operating system as the main target of malware attacks. Attackers can modify application code by entering malicious code, repacking the application and publishing the application in the Android application market. The malware samples used in this study were Judy adware and Marcher banking trojans. This study aims to determine the behavior or characteristics of the malware samples using static and dynamic analysis. The analysis shows that Judy committed ad-fraud by clicking on advertisements without the user's knowledge and Marcher had the ability to collect credential information from the victim's financial account.